The Semantics of Participant Types in Derived Verbs in Nandi - A. Creider, Chet (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 2002)
AbstractThe semantics of three valency-changing verbal derivational suffixes in Nandi (a Nilo-Saharan language spoken in East Africa) are investigated. Two cases of polysemy and one of homonymy are found and related to general case theory (DeLancey 2000, Jakobson 1936, 1990) as well as to the general theory of concept formation (Rosch and Mervis 1996).